Informal Regulation of Industrial Pollution in Developing Countries: Evidence from Indonesia - Pargal, Sheoli; Wheeler, David (Journal of Political Economy, 1996)
When formal regulation is weak or absent, communities often use other channels to induce pollution abatement by local factories in a process of 'informal regulation.' The resulting 'pollution equilibrium' reflects the relative bargaining power of the community and the plant. This note uses Indonesian data from 1989-90 on plant-level organic water pollution to test the informal regulation hypothesis. Copyright 1996 by University of Chicago Press.